Solve for X
8x - 2 = 6 + 10(x - 5)
2 answers:
Answer: x = 21
Step-by-step explanation:
Step 1: Simplify both sides of the equation.
8x−2=6+10(x−5)
8x+−2=6+(10)(x)+(10)(−5)(Distribute)
8x+−2=6+10x+−50
8x−2=(10x)+(6+−50)(Combine Like Terms)
8x−2=10x+−44
8x−2=10x−44
Step 2: Subtract 10x from both sides.
8x−2−10x=10x−44−10x
−2x−2=−44
Step 3: Add 2 to both sides.
−2x−2+2=−44+2
−2x=−42
Step 4: Divide both sides by -2.
−2x / -2 = -42 / -2
x=21
Answer:
x = 21
Step-by-step explanation:
8x - 2 = 6 + 10(x - 5)
Step 1: Distribute the right side of the equation ("6 + 10(x - 5)") so it'll be easier to find x.
8x - 2 = 6 + 10x - 50
8x - 2 = 10x - 44
Step 2: Subtract 8x from both sides
8x - 2 = 10x - 44
<u>-8x -8x</u>
-2 = 2x - 44
Step 3: Add 44 to both sides to get 2x alone.
-2 = 2x - 44
<u>+44 +44</u>
42 = 2x
Step 4: Divide both sides by 2 to get x alone
<u>42</u> = <u>2x</u>
2 2
x = 21
You might be interested in
There are 2 choices for the first set, and 5 choices for the second set. Each of the 2 choices from the first set can be combined with each of the 5 choices from the second set. Therefore there are 2 times 5 combinations from the first and second sets. Continuing this reasoning, the total number of unique combinations of one object from each set is:
Answer:
3
Step-by-step explanation:
Answer:
answer = -12
Step-by-step explanation:
substitute y as -3 and z as 4
3(-3) - 2(4) + 5
-9-8+5
-17+5
-12
28 + 18 - pai, <span>atualmente 28+18+18= 64 -soma64 </span>